Mixed stock analysis identifies natal origins of green turtles at foraging grounds in southeastern Australia - Day, Joanna; Hall, Jane; Rose, Karrie; Vinette Herrin, Kimberly; March, Duane; Pitt, Olly; FitzSimmons, Nancy N.; Hall, Libby; Marshall, Kieran; Iredell, Sigrid; Meagher, Phoebe (Frontiers in Marine Science, 2024)
Identifying critical habitats for marine turtles and connectivity between genetic stocks and the foraging grounds they use is a conservation priority worldwide. Green turtles (Chelonia mydas) are impacted by a wide range of anthropogenic threats that can vary by geographic region and the ontogenetic stage of the individual. In Australia, the strengthening of the East Australian Current due to climate change is increasing ocean temperatures, particularly in southern New South Wales (NSW), which is having large-scale impacts on the distribution and abundance of marine resources. Green turtles are frequently observed in temperate southern NSW waters, but our knowledge of their habitat use, migration patterns and the impact of threatening processes is limited. To assess the origins of green turtles from foraging grounds in southeastern Australia, samples were obtained from green turtles of all size classes (post-hatchlings to adults) that had stranded along an 870 km expanse of the NSW coast and Lord Howe Island between 1997 and 2021. Mitochondrial DNA control region sequences for 283 individuals were compared to 25 potential source genetic stocks in the Indo-Pacific using mixed-stock analysis. A total of 26 haplotypes were identified in NSW, of which 14 had been previously observed at a rookery, eight had been identified previously, but not at a rookery (i.e. orphan haplotypes), and four were previously undescribed. Mixed-stock analysis revealed that NSW waters support multiple genetic stocks but are dominated by those of the Southern Great Barrier Reef and New Caledonia genetic stocks. A small proportion of green turtles originated from more distant stocks in the Indo-Pacific region. Understanding the connectivity between green turtle rookeries and foraging grounds provides an opportunity to 2 assess the impact of anthropogenic threats to turtle stocks, and in turn, prioritize management actions for the conservation of green turtles across regional, national and international jurisdictions.